The wealth of ideas : a history of economic thought - Roncaglia, Alessandro (Cambridge University, 2013)
Illustrates the history of economic thought from antiquity to the present day. Eloquently written and scientifically rigorous, this well documented book focuses on the different views of the economy and society and on their evolution over time. Critically evaluates the scarcity-utility approach in comparison with the Classical/Keynesian approach.